MODIS and determination the threshold of cloud seeding in Kermanshah - Sajjadi, S. Ameneh (2008)
The present study was carried out within four years period covering from 2000 to 2003 where the amount of rainfall in Western Iran (Kermanshah) was recorded by precipitation stations. PW was calculated using the data obtained through MODIS satellite. Using the curve and upon choosing the fittest index PW as independent variable and the rainfall average precipitation (P) as dependent variable, from among the PW, the suitable cloud seeding threshold was estimated. The thresholds obtained through MODIS for cloud seeding and PW were compared across 17 cases. This method employed showed high correlation. The thresholds obtained were 12 mm. With these factors (PW and P) we can study on threshold of cloud seeding.